2014
DOI: 10.1523/jneurosci.2327-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Transporter Genotype Is Associated with a Lateralized Resistance to Distraction during Attention Selection

Abstract: Although lateral asymmetries in orienting behavior are evident across species and have been linked to interhemispheric asymmetries in dopamine signaling, the relative contribution of attentional versus motoric processes remains unclear. Here we took a cognitive genetic approach to adjudicate between roles for dopamine in attentional versus response selection. A sample of nonclinical adult humans (N ϭ 518) performed three cognitive tasks (spatial attentional competition, spatial cueing, and flanker tasks) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…That is, must an aspiring young football player possess an essential neurocognitive capacity like interference control in order to develop that particular skill through practice and training or is that basic capacity developed exclusively through practice and training? Existing research utilizing various imaging and electrophysiological techniques shows that variation in the proficiency of resolving response conflict among non-athlete healthy adults is linked to specific genetic influences, neuromodulators, and individual differences in patterns of neural activity in cognitive control circuitries ( Kopp et al, 1996 ; Casey et al, 2000 ; Hazeltine et al, 2000 ; Bunge et al, 2002 ; Forstmann et al, 2008 ; Ochsner et al, 2009 ; Badgaiyan and Wack, 2011 ; Biehl et al, 2011 ; Newman et al, 2014 ; Chen et al, 2015 ). Outside of efforts to train these skills in children and, in particular, children with attention-deficit hyperactivity disorder, minimal work has focused on the trainability or modifiability of response conflict control skills in adults.…”
Section: Discussionmentioning
confidence: 99%
“…That is, must an aspiring young football player possess an essential neurocognitive capacity like interference control in order to develop that particular skill through practice and training or is that basic capacity developed exclusively through practice and training? Existing research utilizing various imaging and electrophysiological techniques shows that variation in the proficiency of resolving response conflict among non-athlete healthy adults is linked to specific genetic influences, neuromodulators, and individual differences in patterns of neural activity in cognitive control circuitries ( Kopp et al, 1996 ; Casey et al, 2000 ; Hazeltine et al, 2000 ; Bunge et al, 2002 ; Forstmann et al, 2008 ; Ochsner et al, 2009 ; Badgaiyan and Wack, 2011 ; Biehl et al, 2011 ; Newman et al, 2014 ; Chen et al, 2015 ). Outside of efforts to train these skills in children and, in particular, children with attention-deficit hyperactivity disorder, minimal work has focused on the trainability or modifiability of response conflict control skills in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Thus they showed evidence in healthy individuals of a genetically mediated bias in spatial attention that is related to DA signaling. A very recent study with normal human adults showed that allelic variation in a common polymorphism of the DAT1 gene was linked to a lateralized attention but not to response selection (Newman et al, 2014). That is, DNA variation in a putatively functional DA polymorphism was associated with enhanced attentional selection, particularly for stimuli presented within the left hemifield.…”
Section: Neurobiological or Neurogenetic Bases Of The Visuospatialmentioning
confidence: 99%
“…rTPJ) in response to video format is an additional outcome predictor. Third, the 10R DAT1 allele is associated with high risk for ADD (Cook et al, 1995; Gill et al, 1997; Gizer et al, 2009; Kebir et al, 2009; Newman et al, 2014), addiction (Stolf et al, 2014) and poorer outcomes of smoking-cessation treatment (Lerman et al, 1999; O’Gara et al, 2007; Stapleton, Sutherland, & O’Gara, 2007). The present study adds a neurobiological dimension to this literature by showing that 10/10 smokers may have less effective cognitive processing of smoking-cessation videos and may derive less benefit from population-level public health interventions than other smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The 10R/10R homozygosity has been linked to a higher level of novelty seeking, a trait that indicates greater reactivity to novel external stimulation (Sabol et al, 1999). The 10R allele has also been consistently implicated in increased susceptibility to attention deficit disorder (ADD) (Cook et al, 1995; Gill, Daly, Heron, Hawi, & Fitzgerald, 1997; Gizer, Ficks, & Waldman, 2009; Kebir, Tabbane, Sengupta, & Joober, 2009; Newman et al, 2014). Although it remains unclear whether this association is mediated by the dopamine or dopamine transporter levels (Yang et al, 2007), it suggests that homozygous 10R allele carriers are more likely than others to exhibit poor attentional processing, e.g.…”
Section: Introductionmentioning
confidence: 99%